1971
DOI: 10.1111/j.1471-0528.1971.tb00282.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Oestriol in Pregnancy

Abstract: Summary Total plasma oestriol in pregnancy was estimated by a competitive protein binding method. The advantages of the measurement of plasma oestriol levels over the 24‐ or 48‐hour urinary oestriol assays are discussed. The pattern of plasma oestriol levels in the third trimester of pregnancy was investigated in over 400 healthy women and in general a uniform increase was found from the 28th week until term. Diurnal variation was found to be present, but this did not preclude the use of the method for assessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
2

Year Published

1971
1971
1980
1980

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 16 publications
3
16
2
Order By: Relevance
“…The fact that there was no difference in levels of oestriol in plasma in relation to meals supports the view that diet does not influence the level of oestriol. This finding has also been reported by Macourt et al (1971).…”
Section: Resultssupporting
confidence: 86%
“…The fact that there was no difference in levels of oestriol in plasma in relation to meals supports the view that diet does not influence the level of oestriol. This finding has also been reported by Macourt et al (1971).…”
Section: Resultssupporting
confidence: 86%
“…This was in agreement with the results of Macourt et al (1971), who recorded less than 12.5 % variation in patients without renal problems in similar circumstances, but differed from those of Roy (1962) who had earlier concluded that hospitalization and bed rest resulted in a fall in plasma total oestrone and total oestradiol-17,8.…”
Section: Oestrogens In Peripheral Plasmasupporting
confidence: 91%
“…Subsequently these workers were unable to confirm these results in another group of patients (Levitz et al, 1974). A small diurnal variation (approximately 10%) was noticed in three out of five patients by Macourt et al (1971) who claimed that it was not great enough to preclude the use of the method for clinical assessment of the fetoplacental unit. A lack of diurnal variation has also been reported for plasma unconjugated oestradiol-17,8 (Tulchinsky and Korenman, 1971) and unconjugated oestriol ) and for plasma total oestriol (Masson and Wilson, 1972).…”
Section: Oestrogens In Peripheral Plasmamentioning
confidence: 74%
See 1 more Smart Citation
“…However, because urinary E3 especially conjugated E3 is influenced by diurnal and positional variations and require 24hr specimens, various conditions must be stipulated in order to establish a criteria for clinical significance of E3 in urine (Macourt et al, 1971;Bird and Reeves, 1969;Stewart et al, 1970;Selinger and Levitz, 1969;Ricky, 1966). In contrast, plasma unconjugated E3 increases similarly to urinary E3 and is not affected as easily by varying conditions.…”
Section: Practicality Of Methodsmentioning
confidence: 99%